Figures 93–106 in Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms ... - Al-Handal, Adil Y.; Torstensson, Anders; Wulff, Angela (Zenodo, 2022)
Figures 93–106: Marine benthic diatoms in Potter Cove, King George Island, Antarctica in summer 2015. (93) Nitzschia angularis. (94, 95) Nitzschia australis. (96) Nitzschia mitchelliana. (97) Nitzschia cf. gelida. (98) Nitzschia hybrida. (99) Nitzschia cf. obtusa. (100) Nitzschia sigma. (101) Nitzschia sp. (102) Entomoneis gigantea. (103) Entomoneis kjellmanii. (104) Entomoneis paludosa. (105) Surirella fastuosa. (106) Surirella sp. ... : Published as part of Al-Handal, Adil Y., Torstensson, Anders & Wulff, Angela, 2022, Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms, pp. 81-103 in Botanica Marina (Warsaw, Poland) 65 (2) on page 96, DOI: 10.1515/bot-2021-0066, http://zenodo.org/record/11000147 ...